In vitro Interactions of Chicken Programmed Cell Death 1 (PD-1) and PD-1 Ligand-1 (PD-L1) - Reddy, Vishwanatha R. A. P.; Mwangi, William; Sadigh, Yashar; Nair, Venugopal (Frontiers in Cellular and Infection Microbiology, 2019)
In the present study, chicken PD-1 (chPD-1) and PD-L1 (chPD-L1) was in vitro characterized, their binding interactions determined, and respective specific monoclonal antibodies developed. ChPD-1 and chPD-L1 sequence identities and similarities were lower compared with humans and other mammalian species. Further, phylogenetically chPD-1 and chPD-L1 were grouped separately from the mammalian PD-1 and PD-L1 sequences. ChPD-1 and chPD-L1 sequences contain signal peptide, extracellular domain, a transmembrane domain, and intracellular domain, which is similar to other species. Based on three dimensional (3D) structures homology, chPD-1 and chPD-L1 were similar to 3D structures of mammalian PD-1 and PD-L1. Further, Ig V domain of chPD-1 and the Ig V and Ig C domains of chPD-L1 were highly conserved with mammalian counterparts. Superparamagnetic Dynabeads® based binding interactions confirmed that recombinant soluble chPD-1/PD-L1 fusion proteins and surface chPD-1/PD-L1 proteins bind each other on in vitro COS cells. Two monoclonal antibodies specific against chPD-1 and five antibodies against chPD-L1 were developed and characterized by immunofluorescence staining and Western blotting.